Desde el Sur journal guidelines for the authors of articles - ., Universidad Científica del Sur (2019)
Desde el Sur, a journal edited by the General Courses Coordination ofUniversidad Científica del Sur (UCSUR), is a peer-reviewed semi-annual publication.It features previously unpublished research articles from all overthe world in the fields of humanities and social sciences, preferably with afocus on Latin American issues. Desde el Sur is distributed free of charge inboth its printed and online versions.